From the geography of politics to the politics of geography - Stefano Guzzini (Danish Institute for International Studies (DIIS), 2020)
The DIIS Working Paper 'From the geography of politics to the politics of geography' is the English version of the preface for the Brazilian edition of A return of geopolitics in Europe?. The book originally published with Cambridge University Press was translated by Bárbara Motta and published at the University Press of the Universidade Estadual Paulista (Editora Unesp) in S\~ao Paulo. The preface introduces the critical thesis of the political effect that the return of geopolitical thought had in Europe in the 1990s, well before 9/11. The rise of geopolitical thought can be linked to the disorientation, the foreign policy identity crises in many European countries when the end of the Cold War took away the stable coordinates of the post-1945 European security order. Its rise has, however, two pernicious consequences. First, it reverses Clausewitz by making politics the prolongation of war by other means. In other words, it militarises politics, as Aron had already criticised during the Cold War. Second, it essentialises physical and human geography, which justifies the homogenising of identities. The book does not claim that this European experience is universal, but invites scholars in Brazil to contrast it with the specificities of their political discourse and practice, the different nature of foreign policy identity crises and processes of militarisation in Latin America.
Keywords: 330; Geopolitik; Politikwissenschaft